Replication/Assembly Defective Avian Flavivirus With Internal Deletions in the Capsid Can Be Used as an Approach for Living Attenuated Vaccine - He, Yu; Wang, Xiaoli; Guo, Jiaqi; Mao, Li; Zhang, Senzhao; Hu, Tao; Wang, Mingshu; Jia, Renyong; Zhu, Dekang; Liu, Mafeng; Zhao, Xinxin; Yang, Qiao; et al. (Frontiers in Immunology, 2021)
Avian Tembusu virus (TMUV) is a novel flavivirus causing severe egg drop and fatal encephalitis in avian in Asia. In the present study, we screened the structural and functional requirements of TMUV capsid protein (CP) for viral morphogenesis using reverse genetics methods in combination with replicon packaging assays. TMUV-CP showed dramatic functional and structural flexibility, and even though 44 residues were removed from the N-terminus, it was still capable of packaging replicon RNA; in addition, 33 residues were deleted from the C-terminus (containing nearly the entire α4-helix), and infectious particles were still produced, although α4-α4’ is supposedly vital for CP dimerization and nucleocapsid formation. We further analyzed two mutants (ΔC20-43 and ΔC64-96 viruses) with relatively large deletions that still replicated well in BHK-21 cells. Our data indicate that internal deletions within CP impaired viral replication or assembly, resulting in attenuated virus proliferation in cells and attenuated virulence in duck embryos, and these deletion mutations are quite stable in cell culture. An in vivo assay indicated that both ΔC20-43 virus and ΔC64-96 virus were highly attenuated in ducklings but still immunogenic. Single-dose immunization with ΔC20-43 virus or ΔC64-96 virus could protect ducklings from a lethal challenge with good antigen clearance. Together, our data shed light on replication/assembly defective TMUV with internal deletions in CP and provide an effective approach to attenuate viral virulence in live vaccines without changing the antigen composition.